Biological synthesis of metallic nanoparticles using algae. Issue 3 (1st September 2013) - Castro, Laura; Blázquez, María Luisa; Muñoz, Jesus Angel; González, Felisa; Ballester, Antonio
Abstract : The increasing demand and limited natural resources of noble metals make its recovery from dilute industrial wastes attractive, especially when using environmentally friendly methods. Nowadays, the high impact that nanotechnology is having in both science and society offers new research possibilities. Gold and silver nanoparticles were biosynthesised by a simple method using different algae as reducing agent. The authors explored the application of dead algae in an eco‐friendly procedure. The nanoparticle formation was followed by UV–vis absorption spectroscopy and transmission electron microscopy. The functional groups involved in the bioreduction were studied by Fourier transform infrared spectroscopy.